AKULTURASI BUDAYA CINA DAN ISLAM DALAM ARSITEKTUR TEMPAT IBADAH DI KOTA LASEM, JAWA TENGAH - Diah Ayuningrum (Sabda: Jurnal Kajian Kebudayaan, 2017)
The Interaction of Chinese culture and Islam has been going on since four hundred years ago. Tolerance between indigenous people, Chinese, and Moslem is well preserved until now. One of them is the architectural town of Lasem and the house in China town area - a typical Chinese style house found in Lasem. Homes, places of worship like temples are also typical Chinese style also prove the occurrence of cultural acculturation in Lasem. The roof of Masid Jami Lasem is a major proof of acculturation between Islamic and Chinese culture